The boomerang of Female40: Seniority pensions in Hungary, 2011-2018 - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2018)
In 2011, the Hungarian government introduced seniority pensions (Female40): females, who have been accumulating at least 40 years of eligibility (related to the length of contributions), can retire at any age without actuarial benefit reduction. The elimination of other early retirement scheme in 2012 and slowly rising real wages made the program even more popular: the lifetime benefit was maximized at the earliest retirement. Since 2016, real wages have been growing rather fast; making delay attractive. Without being recognized, Female40 has become a boomerang: immediate retirement from 2014 causes loss rather than gain to the retiree of Female40.
Keywords: H55; 330; public pension; early retirement; seniority pensions; optimal retirement age